2012
DOI: 10.7785/tcrt.2012.500230
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Access Spine Surgery (MASS) for Decompression and Stabilization Performed as an Out-Patient Procedure for Metastatic Spinal Tumours Followed by Spine Stereotactic Body Radiotherapy (SBRT): First Report of Technique and Preliminary Outcomes

Abstract: We report a novel approach in the treatment of spinal metastases with epidural disease and mechanical instability using a combined minimal access spine surgery (MASS) technique followed by spine stereotactic body radiotherapy (SBRT). This study was performed as a retrospective review of the first ten consecutive patients treated with this combined approach.The MASS technique was based on a tubular retraction system to gain access for decom pression and mechanical stabilization achieved using methylmethacrylate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 22 publications
1
48
0
Order By: Relevance
“…They reported one wound complication. Several smaller case reports and series are also available [37,[41][42][43].…”
Section: Discussionmentioning
confidence: 95%
“…They reported one wound complication. Several smaller case reports and series are also available [37,[41][42][43].…”
Section: Discussionmentioning
confidence: 95%
“…Recently, Massicotte et al reported on the role of minimal access spine surgery (MASS) in a small series as an adjunct to definitive SBRT with a median time between surgery and irradiation of only 7 days. 39 The median total radiation dose was 24 Gy (range, 18-35 Gy), in a mean of 3 fractions (range, 1-5). With a median follow-up for the cohort of 13 months (range, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], local control based on imaging was achieved in 7 of the 10 patients treated.…”
Section: High-dose Spinal Rt In the Adjuvant Settingmentioning
confidence: 99%
“…[91011121314151617] However, there is a paucity of literature on the concomitant use of MIS separation surgery and adjuvant SBRT. [14] In this paper, we describe the various minimally invasive surgical techniques employed to achieve separation surgery and spinal stabilization followed by postoperative stereotactic radiotherapy.…”
Section: Introductionmentioning
confidence: 99%